Occupational hand dermatitis in car repair workers - Mohammad Javad Zare Sakhvidi; Ziba Loukzadeh; Hamid Dehghan Tezerjani (AIMS Press, 2019)
Introduction: Exposure to used gasoline engine oils during oil change and other automobile repair services is common for many mechanics, electrical technicians, and other car service workers. We aimed to determine the prevalence of hand dermatitis in car repair workers with different specialty and actual dermal exposure hazards in the workplace. Methods: We examined the dermal problems in 153 male car repair workers and compared it to 140 office workers. Exposed and control groups were administered a Nordic Occupational Skin Questionnaire. Dermal exposure score also was calculated. Results: The prevalence of hand dermatitis in car repair workers (19.0%) was significantly higher than office worker (7.9%) [OR: 2.74, (95% CI = 1.31, 5.73)] and also higher than general population. Prevalence of atopic dermatitis was significantly higher in exposed group that had hand dermatitis compared with those who had no hand dermatitis (P < 0.001). The highest hand dermatitis as well as actual dermal exposure was observed in the mechanics and transmission technician respectively. Conclusion: Car repair workers have an elevated prevalence of hand dermatitis in comparison with office workers. The most important risk factors for hand dermatitis among car repair workers are atopic dermatitis and the next the level of skin exposure to potential skin hazards.